Management of St. Croix Sheep and Garut Sheep Genetic Resources in Sheep Formation - U. Adiati; S. Rusdiana (Jurnal Sain Peternakan Indonesia, 2022)
This study aimed to determine the management of the genetic resources of St. Croix sheep and Garut sheep in the formation of sheep clumps and their physiological conditions. The study was conducted at the Livestock Research Institute on Jalan Raya Pajajaran Bogor, West Java, in 2019. Ex-situ collection materials and characterization of St. Croix sheep and Garut sheep were as many as 250 heads; sheep breeding was carried out in groups; one male married 5-10 heads. The rams were left in the mating group for two oestrus cycles (34 days). Primary data and secondary data were analyzed descriptively and quantitatively. The results were obtained in the germplasm research of St. Croix with an average mating body weight of 23.45 ± 4.08 kg and Garut sheep of 26.20 ±  4.92 kg. The average birth weight of St. Croix sheep was 2.26+0.35 kg, and Garut sheep was 2.05± 0.47kg. The establishment of the St. Croix and Garut sheep have high genetic quality, production, and reproductive characteristics, but each has a different productivity level. The study of germplasm preservation of sheep was carried out to increase the population of St. Croix sheep and pure Garut sheep so that the maximum target population of >200 sheep was achieved to meet the demand for seeds as animal food.